Applying the Aboveground-Belowground Interaction Concept in Agriculture: Spatio-Temporal Scales Matter - Veen, G. F.; Wubs, E. R. Jasper; Bardgett, Richard D.; Barrios, Edmundo; Bradford, Mark A.; Carvalho, Sabrina; De Deyn, Gerlinde B.; de Vries, Franciska T.; Giller, Ken E.; Kleijn, David; Landis, Douglas A.; Rossing, Walter A. H.; et al. (Frontiers in Ecology and Evolution, 2019)
Interactions between aboveground and belowground organisms are important drivers of plant growth and performance in natural ecosystems. Making practical use of such above-belowground biotic interactions offers important opportunities for enhancing the sustainability of agriculture, as it could favour crop growth, nutrient supply, and defence against biotic and abiotic stresses. However, the operation of above- and belowground organisms at different spatial and temporal scales provides important challenges for application in agriculture. Aboveground organisms, such as herbivores and pollinators, operate at a spatial scales that exceeds individual fields and are highly variable in abundance within growing seasons. In contrast, pathogenic, symbiotic, and decomposer soil biota operate at much more localized spatial scales from individual plant species to patches of square metres, however, they generate legacy effects on plant performance that may last from single to multiple years. The challenge is to promote pollinators and suppress pests at the landscape and field scale, and connect these by creating positive legacy effects of local plant-soil interactions for next generations of plants. The aim of the present paper is to explore where current ecological knowledge on above- and belowground biotic interactions can be used to increase agricultural sustainability. Then, we highlight the need to explicitly consider the spatio-temporal scales at which aboveground and belowground organisms operate. We identified that successful integration of above-belowground biotic interactions requires developing crop rotations and intercropping systems that create positive local soil legacy effects for neighbouring as well subsequent crops. These configurations may then be used as building blocks to design landscapes that accommodate beneficial aboveground communities with respect to their required resources. For successful adoption of above-belowground interactions in agriculture there is a need for context-specific solutions, as well as sound socio-economic embedding.